Three-parent children: an overview of ethical positions on „mitochondrial replacement” techniques - Jaranowski, Paweł (Studia Ecologiae et Bioethicae, 2017)
The article presents the ethical debate that begun in Great Britain in 2015 on “mitochondrial replacement” (also called “mitochondrial donation”) before implementing those new methods of medically assisted reproduction into clinical practice. It begins with introducing current British legal norms, allowing for the first time in history to induce hereditable modifications in the human genome – precisely in its mitochondrial part – during “in vitro” fertilization. The second part is devoted to medical issues. It accounts for: elements of human cytology; pathology, epidemiology, and symptoms of mitochondrial disorders; description of “mitochondrial replacement” techniques. The third part is dedicated to philosophical issues. I discuss naturalis, transhumanist, and personalist ethical assessments of new technologies, revealing their anthropological assumptions. Examples of such arguments come from an open debate carried out by Nuffield Council on Bioethics.